Longitudinal exploration of cancer-related cognitive impairment in patients with newly diagnosed aggressive lymphoma: protocol for a feasibility study - Vincent Dore; Christopher C Rowe; Meinir Krishnasamy; Haryana Dhillon; Adam K Walker; Karla Gough; Priscilla Gates; Carlene Wilson; Eliza Hawkes; Yuliya Perchyonok; Janette L Vardy; Michiel de Ruiter (BMJ Open)
Introduction Cancer-related cognitive impairment (CRCI) is a distressing and disabling side-effect of cancer treatments affecting up to 75% of patients. For some patients, their cognitive impairment may be transient, but for a subgroup, these symptoms can be long-standing and have a major impact on the quality of life. This paper describes the protocol for a study: (1) to assess the feasibility of collecting longitudinal data on cognition via self-report, neuropsychological testing, peripheral markers of inflammation and neuroimaging and (2) to explore and describe patterns of cancer-related cognitive impairment over the course of treatment and recovery in patients with newly diagnosed, aggressive lymphoma undergoing standard therapy with curative intent.Methods and analysis This is a prospective, longitudinal, feasibility study in which 30 newly diagnosed, treatment-naive patients with aggressive lymphoma will be recruited over a 12-month period. Patients will complete comprehensive assessments at three time points: baseline (time 1, pre-treatment) and two post-baseline follow-up assessments (time 2, mid-treatment and time 3, 6–8 weeks post-treatment completion). All patients will be assessed for self-reported cognitive difficulties and objective cognitive function using Stroop Colour and Word, Trail Making Test Part A and B, Hopkins Verbal Learning Test-Revised, Controlled Oral Word Association and Digit Span. Blood cell-based inflammatory markers and neuroimaging including a positron emission tomography (PET) with 18F-labelled fluoro-2-deoxyglucose (18F-FDG) and CT (18F-FDG-PET/CT) and a MRI will explore potential inflammatory and neuroanatomical or functional mechanisms and biomarkers related to CRCI. The primary intent of analysis will be to assess the feasibility of collecting longitudinal data on cognition using subjective reports and objective tasks from patients during treatment and recovery for lymphoma. These data will inform the design of a larger-scale investigation into the patterns of cognitive change over the course of treatment and recovery, adding to an underexplored area of cancer survivorship research.Ethics and dissemination Ethical approval has been granted by Austin Health Human Rights Ethics Committee (HREC) in Victoria Australia. Peer reviewed publications and conference presentations will report the findings of this novel study.Trial registration number Australian New Zealand Clinical Trials Registry (ACTRN12619001649101).